Catalytic direct oxidation of methane to methanol by redox of copper mordenite. Issue 10 (26th March 2021) - Ohyama, Junya; Hirayama, Airi; Tsuchimura, Yuka; Kondou, Nahoko; Yoshida, Hiroshi; Machida, Masato; Nishimura, Shun; Kato, Kazuo; Miyazato, Itsuki; Takahashi, Keisuke
Abstract : Catalytic production of CH3 OH by direct oxidation of CH4 with O2 was performed using Cu zeolites in a CH4 /O2 /H2 O flow reaction, where Cu-MOR exhibited relatively high CH3 OH production with the redox of Cu(i )/Cu(ii ) species. Abstract : Expectations for industrial implementation of direct conversion of CH4 to CH3 OH are growing with the increasing demand for energy-efficient chemical processes. In this study, catalytic production of CH3 OH by direct oxidation of CH4 with O2 was performed using Cu zeolite catalysts in a CH4 /O2 /H2 O flow reaction. Among the various Cu zeolites investigated, the Cu-MOR catalyst exhibited relatively high CH3 OH production with a turnover number of 7.4 molCH3 OH molCu −1 over 24 h (CH4 conversion: 0.011%). The catalytically active Cu species and catalytic cycle were investigated by in situ simultaneous X-ray absorption and infrared spectroscopy. The results suggest that the key to the catalytic cycle over Cu-MOR is the redox of Cu(i )/Cu(ii ) species. Furthermore, H2 O-adsorption-included dynamic Cu species are revealed to be catalytically active.